Anisotropic rock physics characteristics and patterns of pore-fracture type tight sandstone reservoirs - Juncheng Dai; Yuanyuan Yan; Wei Wei; Cheng Xi; Guangguang Yang; Jun Yao (Frontiers in Earth Science)
Exploration and development of tight gas reservoirs are pivotal in augmenting oil and gas reserves and production. Tight sandstone reservoirs, characterized by intricate geological environments, nuanced physical property variations, substantial fluid heterogeneities, and ambiguous seismic rock physics responses, necessitate a departure from conventional isotropic reservoir sensitivity parameters. This study introduces an innovative lithofacies identification strategy and methodology grounded in anisotropic rock physics sensitivity parameters. The investigation revolves around 20 core samples from the fourth member of the Xujiahe Formation in Jianyang. A multi-scale approach, encompassing imaging logging, core analysis, porosity/permeability measurements, and cast thin section examinations, was employed to classify the samples into four distinct categories: dry and water-saturated pore types, alongside dry and water-saturated fractured pore types. Subsequently, an enhanced full-angle ultrasonic anisotropy testing system was utilized to conduct multi-directional acoustic wave measurements. The results revealed that gas-bearing fractured pore samples exhibit pronounced velocity and amplitude anisotropy, setting them apart from other lithofacies types. To quantify these distinguishing features, a rock physics template encompassing P-wave anisotropy (ε) and amplitude anisotropy (εA) parameters was established. By setting thresholds for ε and εA (>20%), the dry fractured pore lithofacies can be effectively discriminated. Moreover, leveraging the full-angle waveform similarity coefficient spectrum, we used a special parameter, εslow, for slowness anisotropy, along with its theoretical derivation. Notably, water-saturated pore types exhibited slowness anisotropy parameters consistently below 0.01. Integration of the (λρ-μρ) template and its thresholds (λρ < 60 & μρ < 30) further facilitated the selection and differentiation of all four lithofacies types. These research outcomes contribute significantly to advancing the prediction of tight sandstone reservoirs and fluid identification, offering a robust framework for future exploration endeavors.